الأمم المتحد ة مرجع ممارسات مجلس الأمن: ملحق 2020 - United Nations Department of Political; Peacebuilding Affairs (United Nations, 2023)
The Repertoire of the Practice of the Security Council provides UN Member States, UN entities, researchers and the general public a comprehensive, reliable, objective and readily accessible source of information regarding the evolving practice of the Security Council on constitutional, procedural and substantive matters since inception in 1946. The Repertoire covers in particular the Council’s interpretation and application of the UN Charter and its own Provisional Rules of Procedure and features case studies as well as summaries of its official documents.